Pengembangan Strategi Industri Kreatif Sangkar Burung di Kecamatan Bogor Barat Menghadapi Persaingan Global - Amelia Oktrivina; Indah Masri; Iha Haryani Hatta; Yuana Rizky; Octaviani Mandagie; Mulyadi Mulyadi; Cotoro Mukri (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
The birdcage industry in West Bogor Subdistrict has immense growth potential. However, it faces several challenges that need to be addressed. This study aims to create an effective strategy for addressing competition through SWOT analysis. A descriptive and qualitative approach was used to depict the industry's condition and analyze internal and external factors that impact its performance. The findings reveal that the birdcage industry possesses strengths in product quality and an experienced workforce but also faces weaknesses such as limited production tools and access to international markets. Opportunities include local market and government support, while threats mainly arise from international competition and fluctuating raw material prices.